Numbers, Numbers Everywhere - Northcott, Richard (Oxford University Press, 2005)
This interactive series makes developing language skills exciting for primary. Stories and cross-curricular texts with full-color illustrations stimulate students' interest, while carefully graded English introduces them to new language